The interaction and pathogenesis between cognitive impairment and common cardiovascular diseases in the elderly - Wenhang Zuo; Jinhui Wu (SAGE Publishing, 2022)
Both cognitive impairment and cardiovascular diseases have a high incidence in the elderly population, increasing the burden of care and reducing the quality of life. Studies have suggested that cognitive impairment interacts with cardiovascular diseases such as coronary heart disease, abnormal blood pressure, heart failure, and arrhythmia. On one hand, cognitive impairment in the elderly influences the progression and self-management of cardiovascular diseases and increases the risk of cardiovascular-related adverse events. On the other hand, coronary heart disease, heart failure, higher blood pressure variability, orthostatic hypotension, and atrial fibrillation may aggravate cognitive impairment. The role of blood pressure levels on cognition remains controversial. Several shared biological pathways have been proposed as the underlying mechanism for the association. Cardiovascular diseases may lead to cognitive decline even dementia through cerebral perfusion damage, brain structural changes, inflammation, β-amyloid deposition, and neuroendocrine disorders. It is of great significance to study the interaction and put forward effective interventions in an overall perspective to reduce care burden and improve the quality of life of the elderly patients.